PENGARUH LATIHAN KOORDINASI MATA DAN KAKI TERHADAP AKURASI PASSING SEPAK BOLA SSB GUMARANG KU-15 - Fadli Fadillah; Ramdhani Rahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of eye–foot coordination training on passing accuracy among SSB Gumarang U-15 soccer players. Passing is a fundamental technique in soccer; therefore, improving its accuracy is essential. The research employed an experimental method with a one-group pretest–posttest design. The sample consisted of 20 athletes from SSB Gumarang U-15, selected using total sampling. The research instrument was a passing accuracy test with a validity of 0.963 and reliability of 0.900. The results showed that the average pretest score was 5.95, with the lowest score of 3 and the highest of 9, while the posttest average increased to 11.85, with the lowest score of 8 and the highest of 15. The Paired Sample T-Test revealed a significance value of 0.000 < 0.05, indicating a significant difference between pretest and posttest results. Thus, eye–foot coordination training has a positive effect on improving passing accuracy in SSB Gumarang U-15 athletes. These findings recommend that coaches integrate eye–foot coordination training into youth development programs, as it is proven effective in enhancing mastery of soccer’s basic techniques.